Orthopaedic surgery core curriculum: the spine. Issue 978 (2nd April 2007) - Wadey, Veronica M R; Halpern, Jerry; Bouchard, Jacques; Dev, Parvati; Olshen, Richard A; Walker, Decker
Abstract : Objective: To develop a core curriculum for orthopaedic surgery and to conduct a national survey to assess the importance of 281 items in the curriculum. Attention was focused specifically on 24 items pertaining to the curriculum that are pertinent to the spine. Study design: A cross-sectional survey of a random sample of orthopaedic surgeons whose primary affiliation was non-academic, representing the provinces and territories of Canada Methods: A questionnaire containing 281 items was developed. A random group of 131 (out of 156) orthopaedic surgeons whose primary affiliation is non-academic completed the questionnaire. The data were analysed quantitatively using average mean scores, histograms, the modified Hotelling's T 2 test and the Benjimini–Hochberg procedure. Results: 131 of 156 (84%) orthopaedic surgeons participated, in this study. 14 of 24 items were ranked at no less than 3 out of 4 thus suggesting that 58% of the items are important or probably important to know by the end of residency (SD⩽0.07). Residents need to learn the diagnosis and principles of managing patients with common conditions of the spine. Conclusions: The study shows, with reliable statistical evidence, that orthopaedic residents are no longer expected to be able to perform spinal fusions with proficiency on completion of residency. Is the exposure to surgical spine problems and the ability to be comfortable with operating expectations specific to the fellowship level? If so, the focus during residency or increasing accredited spine fellowships needs to be addressed to ensure that enough spine surgeons are educated to meet the future healthcare demands projected for Canada.